A Comparative Study of the Amylin Hormone Levels in the Sera of Hypothyroidism Patients with and Without Type 2 Diabetes Mellitus - Abed, Baydaa Ahmed; Farhan, Layla Othman; Al Sabbagh, Ahmed Abduljabar; Salman, Isam N. (Iraqi Journal of Science, 2024)
The study was designed to compare amylin hormone levels and some biochemical parameters in the serum of Iraqi patient with hypothyroidism (hypo) with and without Type 2 diabetes mellitus (T2DM). This study included ninety subjects and was divided into two patient groups: group I, which included 30 hypo without T2DM, and group II, which included 30 hypo with T2DM. Group III included 30 apparently healthy controls. The age range is 40-60 years. A significant increase in body mass index (BMI), fasting blood glucose (FBG), total cholesterol (TC), low-density lipoprotein (LDL), very low density lipoprotein (VLDL), triglyceride (TG), amylin hormone, and thyroid-stimulating hormone (TSH) in patients with hypo and hypo with T2DM (groups I and II) when compared to healthy controls (group III), and a significant decrease in the level of HDL in patient groups (I and II) when compared to healthy control groups. The amylin hormone receiver operating characteristic (ROC) curve showed a clear cut-off value (45.304 and 2) when calculated in hypo with and without T2DM compared with control groups, respectively. While the ROC curve showed a clear cut-off value (50.661) when compared in hypo with and without T2DM groups. Amylin is a hormone marker of glucose homeostasis, so it may be surrogate novel biomarker for all other traditional biomarkers for the prediction of diabetes and thyroid dysfunction.